Hubungan Ekspansi Sangkar Thoraks Terhadap Vo2 Max Dan Kapasitas Vital Paru Pada Mahasiswa - Naima, Aisyah Lifsantin; Jumiati, Jinten (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
The COVID-19 pandemic in Indonesia is part of the 2019 corona virus disease (covid-19) pandemic that is currently taking place throughout the world. The government's efforts in dealing with the Covid-19 Pandemic by working from home (work from home) and studying from home (study from home) which have an impact on health, one of which is a decrease in the level of physical fitness due to lack of movement. A person's fitness is closely related to aerobic capacity as measured by VO2max. VO2max is influenced by the lungs vital capacity which is also affected by the size of the expanding thoracic cavity. The purpose of this study was to determine correlation between thoracic cage expansion, VO2max and lung vital capacity. A cross-sectional study was conducted involving 44 physiotherapy students who met the inclusion criteria as subjects. Data were analyzed using the Spearman test and the results obtained were ICS 3 with VO2max p=0.002, processus xypoideus with Vo2max p=0.000. While the results of ICS 3 with KVP p=0.003, processus xypoideus with KVP p =0.002. From these results it can be concluded that there is a relationship between thoracic cage expansion to VO2max and lung vital capacity.